Physiological Mechanisms Underlying the High-Grain Yield and High-Nitrogen Use Efficiency of Elite Rice Varieties under a Low Rate of Nitrogen Application in China - Wu, Lilian; Yuan, Shen; Huang, Liying; Sun, Fan; Zhu, Guanglong; Li, Guohui; Fahad, Shah; Peng, Shaobing; Wang, Fei (Frontiers in Plant Science, 2016)
Selecting rice varieties with a high nitrogen (N) use efficiency (NUE) is the best approach to reduce N fertilizer application in rice production and is one of the objectives of the Green Super Rice (GSR) Project in China. However, the performance of elite candidate GSR varieties under low N supply remains unclear. In the present study, differences in the grain yield and NUE of thirteen and fourteen candidate varieties with two controls were determined at a N rate of 100 kg ha-1 in field experiments in 2014 and 2015, respectively. The grain yield for all of the rice varieties ranged from 8.67 to 11.09 t ha-1, except for a japonica rice variety YG29, which had a grain yield of 6.42 t ha-1. HY549 and YY4949 produced the highest grain yield, reflecting a higher biomass production and harvest index in 2014 and 2015, respectively. Total N uptake at maturity (TNPM) ranged from 144 to 210 kg ha-1, while the nitrogen use efficiency for grain production (NUEg) ranged from 35.2 to 62.0 kg kg-1. Both TNPM and NUEg showed a significant quadratic correlation with grain yield, indicating that it is possible to obtain high grain yield and NUEg with the reduction of TNPM. The correlation between N-related parameters and yield-related traits suggests that promoting pre-heading growth could increase TNPM, while high biomass accumulation during the grain filling period and large panicles are important for a higher NUEg. In addition, there were significant and negative correlations between the NUEg and N concentrations in leaf, stem and grain tissues at maturity. Further improvements in NUEg require a reduction in the stem N concentration but not the leaf N concentration. The daily grain yield was the only parameter that significantly and positively correlated with both TNPM and NUEg. This study determined variations in the grain yield and NUE of elite candidate GSR rice varieties and provided plant traits that could be used as selection criteria in breeding N-efficient rice varieties.